The Uses Of Artificial Intelligence In The Economic Operations - Mostefaoui, Ilhem; Benkirat, Widad (جامعة الوادي University of Eloued, 2024)
This study aims to identify the uses of artificial intelligence in the economic institution and by determining each of the functions of the organization from production, marketing, human resources management, accounting and finance because of its great importance in achieving the desired goals of the major institution. This is due to the fact that artificial intelligence has become today an urgent necessity that cannot be ignored in light of the technological developments in the world, especially the dazzling development in the business world, as it was highlighted the uses of Meta Foundation for artificial intelligence and focus on its use in the marketing process. This study found that Meta uses artificial intelligence tools and models in its operations, especially its marketing operations, in order to reach its goals by sweeping the platform market, technological development and research in the field of artificial intelligence, and to achieve huge revenues, especially in the field of advertising, particularly on the Facebook and Instagram platforms.
The uses of artificial intelligence in the economic operations of the enterprise Marketing in Meta company as a model
Keywords: Artificial intelligence; marketing; platforms; advertising; Meta.